New Perspectives on Mental Health Education for College Students in the New Era—A Preliminary Study of Artistic Healing Through Printmaking (Journal of Global Arts Studies, 2025)
Background: As a comprehensive psychological treatment approach, printmaking art therapy integrates psychology, art, and therapeutic practice, and has gradually become a distinctive method in mental health education. Objective: This paper aims to explore the role of printmaking art therapy in the mental health education of college students in the new era. Methods: Through nonverbal artistic creation, participants engage in immersive artistic experiences to express emotions, conduct self-exploration, regulate stress, build self-confidence, and establish social support networks. Results: The multisensory process involved in printmaking enhances participant acceptance, authentically reflects students’ psychological conditions, reduces the stigma associated with mental health issues, and compensates for the limitations of traditional mental health education resources. Conclusion: By combining artistic expression with psychological adjustment mechanisms, printmaking art therapy expands the scope of traditional mental health education practices, offering targeted approaches for emotional regulation and self-awareness enhancement, and demonstrating significant practical value in contemporary college mental health education.
Keywords: Art Therapy; Printmaking Arts; New Era College Students; Mental Health